Temporary self-managing teams: Mythos or logos - Garth V. Brown; Maria Tims; Svetlana N. Khapova (Cogent Psychology)
This study aims to explore the frequency of workers’ participation in modern team types, compare them to each other, and report how participation in the various team types fulfills basic needs satisfaction. An exploratory, cross-sectional study was conducted among employees from the USA. (N = 459) and the UK. (N = 612). Participation in unconventional team types (i.e. temporary, self-managing, and temporary self-managing teams) serves as an independent variable to explore employees’ experiences. Next, we correlate team-type experiences and Basic Need Satisfaction (W-BNS). Evidence suggests that temporary forms of teamwork underperform teams of open-ended duration in meeting basic needs satisfaction. The study reveals that a novel team form, a temporary self-managing team, is understudied yet relatively common in workplaces. Unconventional teams are increasingly common, especially in dynamic industries. However, these teams often under satisfy members compared to permanent, managed teams in meeting psychological needs like autonomy, competence, and relatedness. Organizations must balance innovative team configurations with individual needs. National sampling suggests that unidentified cultural differences are not yet understood, and further investigation is required to explain national/cultural (USA/UK) differences.